Hubungan Tekanan Darah Intradialisis Dengan Kejadian Fatigue Pada Pasien Gagal Ginjal Kronis Yang Menjalani Hemodialisa - Merlianty Anggraeny; Hotma Rumahorbo; Sansri Diah K.D.; Yosep Rohyadi (Jurnal Keperawatan Indonesia Florence Nightingale, 2026)
Chronic Kidney Disease (CKD) affect more 500 million people worldwide,, with 1.5 million undergoing hemodialysis. In Indonesian, the 2018 Health Survey reported a CKD prevalence of 0.18%. Fatigue is a common symptom among CKD patients, particularly those on hemodialysis (60%-97%). This study aimed to examine the relationship between intradialytic blood pressure and fatigue in CKD patients undergoing hemodialysis at RSUD Al-Ihsan. A quantitative study with a cross-sectional analytic correlational design was conducted. Blood pressure was measured using a hemodialysis machine at the first, third, and fifth hours of treatment,. Fatigue was assessed using the FACIT Fatigue Scale questionnaire. A total of 87 patients were selected using probability sampling through a simple random sampling method. The results showed that most respondents were female, aged 45-59 years, and unemployed.Results showed a gradual decrease in blood pressure during dialysis. Pearson correlation analysis revealed no significant relationship between systolic or diastolic blood pressure and fatigue (p-value>0,05 and r< 0,20). Conclusion: Intradialytic blood pressure was not significantly related to fatigue. Recommendation: Nursing care should include fatigue screening, patient education, and attention to nutrition, sleep quality, and physical activity in fatigue management.